Ultrasonic extraction of fish oil from eel - Norasyikin, Che Pi (2009)
The eel is rich in calcium and iron as well as vitamins B and D, also believed by many people to be the cure for kidney disease, asthma, heart palpitations and impotency as well as hastening healing of surgical wounds. In this research, fish oil was extracted from Eel (Monopterus albus) by using ultrasonic extraction method. Effects of different ultrasonic power, solvent to solid ratio and sonication time on extraction yields were investigated. Then, the extracted fish oil was analyzed using 785 DMP Titrino and Gas Chromatography Mass Spectrometer. The ultrasonic power was used at 100, 200, 300 and 450W. The solvents used were 50, 100, 200 and 500ml of ethanol. In terms of sonication time it was set at 20, 30, 50, and 60 minutes. Results obtained show that the ultrasonic power of 200 W, solvent amount of 500 ml and 60 minutes of sonication time produce the higher yields of extracted fish oil 7.20 %. The FFA and acid value content of the extracted fish oil was higher at 100 W of ultrasonic power with content of 0.53 g/100 g and 0.30 MgKOH/1 g. Qualitative analysis Gas Chromatography Mass Spectrometer shows that the compound of Fatty Acid Methyl Ester (FAMEs) which is palmitic and stearic acid were detected. As a conclusion, the objectives in this study were achieved by extract the fish oil from eel using ultrasonic extraction method that effects of different ultrasonic power, solvent to solid ratio and sonication time on extraction yields.